Evaluation of microplastic release caused by textile washing processes of synthetic fabrics. (May 2018) - De Falco, Francesca; Gullo, Maria Pia; Gentile, Gennaro; Di Pace, Emilia; Cocca, Mariacristina; Gelabert, Laura; Brouta-Agnésa, Marolda; Rovira, Angels; Escudero, Rosa; Villalba, Raquel; Mossotti, Raffaella; Montarsolo, Alessio; et al.
Abstract: A new and more alarming source of marine contamination has been recently identified in micro and nanosized plastic fragments. Microplastics are difficult to see with the naked eye and to biodegrade in marine environment, representing a problem since they can be ingested by plankton or other marine organisms, potentially entering the food web. An important source of microplastics appears to be through sewage contaminated by synthetic fibres from washing clothes. Since this phenomenon still lacks of a comprehensive analysis, the objective of this contribution was to investigate the role of washing processes of synthetic textiles on microplastic release. In particular, an analytical protocol was set up, based on the filtration of the washing water of synthetic fabrics and on the analysis of the filters by scanning electron microscopy. The quantification of the microfibre shedding from three different synthetic fabric types, woven polyester, knitted polyester, and woven polypropylene, during washing trials simulating domestic conditions, was achieved and statistically analysed. The highest release of microplastics was recorded for the wash of woven polyester and this phenomenon was correlated to the fabric characteristics. Moreover, the extent of microfibre release from woven polyester fabrics due to different detergents, washing parameters and industrial washes was evaluated. The number of microfibres released from a typical 5 kg wash load of polyester fabrics was estimated to be over 6, 000, 000 depending on the type of detergent used. The usage of a softener during washes reduces the number of microfibres released of more than 35%. The amount and size of the released microfibres confirm that they could not be totally retained by wastewater treatments plants, and potentially affect the aquatic environment. Graphical abstract: Image 1 Highlights: A successful procedure to evaluate microplastics release from fabrics was set up. The amount of microplastics depends on the fabrics, laundry products and washes. An increased amount of microfibres is released by woven polyester. Softener and bleach reduce fibre's damage and breaks. High temperature, washing time and mechanical action increase the microfibre release. Abstract : A successful procedure to quantify the microfibre release from synthetic fabrics was developed. The effect of detergents and washing conditions on the extent of microfibre release was evaluated.